Problems of physical rehabilitation of movement disorders in the pathology of the hip joint in patients with the consequences of a cerebral stroke - О.І. Shkurupіi; І.М. Olexenko; О.L. Smirnova; N.Y. Gryshunina; K.O. Yaroshenko (Medičnì Perspektivi)
The purpose of the work was to analyze the experience of foreign specialists regarding movement and structural disorders of the proximal part of the femur in patients with the consequences of stroke and their impact on the effectiveness of rehabilitation programs for hip joint pathology. To fulfill the goal, an analysis of foreign literary sources was carried out in modern databases: Google Scholar, Web of Science, PubMed, Medline, Cochrane, Pedro. The search depth is 22 years (from January 2000 to October 2021). The analysis of literature sources indicated that limitation of motor activity and axial loads in patients after acute cerebrovascular accident, in particular limitation of mobility in the hip joint, impairment of muscle strength and tone due to hemiparesis can lead to the development of osteoporosis. Particularly important from the point of view of adverse consequences is a decrease in mineral density and fractures of the proximal part of the femur. On the other hand, disturbed biomechanics of movements in the hip joint in persons with the consequences of a cerebral stroke, under the condition of axial load on the limb, can lead to the development of osteoarthritis of the hip joint. Osteoarthritis results in limited mobility of the hip joint, which leads to secondary immobilization of the hip joint and, as a result, can also lead to further osteoporosis. Existing disorders of neuromuscular control, muscle tone and strength, limitation of mobility of the hip joint, including due to spasticity, problems with static and dynamic balance, and, as a result, an increased risk of falling in patients with the consequences of a stroke, can negatively affect the recovery of motor functions, activity limitation, and, as a result, reduce the effectiveness of rehabilitation of patients after hip joint replacement. Existing movement disorders, as a result of a stroke, require the development and justification of new rehabilitation programs, including the use of modern technical means and virtual reality.